Synergistic sp-C/sp-N Anchoring of Metal Single Atoms on Graphdiyne for Enhanced Microwave Absorption - Fan, Yihao; Cheng, Haichuan; Deng, Pengyu; Wu, Jianfeng; Zhang, Baoliang (Nano-Micro Letters, 2026)
Enhancing the conduction and polarization properties of the emerging two-dimensional carbon material graphdiyne (GDY) represents a crucial step in broadening its application in microwave absorption. A novel strategy was proposed to improve the microwave absorption performance of GDY through precise regulation of single-atom structures. Using three-dimensional spherical GDY as a substrate, Two Fe single-atom absorbers were successfully constructed: one anchored by Fe–N-GDY (FeN2C2) via sp-N/sp-C cooperative coordination, and the other anchored by Fe-GDY (FeC4) via sp-C coordination alone. Combined experimental characterization and theoretical calculations revealed that the FeN2C2 configuration induces stronger charge transfer and dipole polarization. This effect synergistically optimizes both the dielectric loss and impedance matching of the material. Consequently, the optimal sample Fe–N-GDY achieved an effective absorption bandwidth of 5.98 GHz at a matched thickness of 2.0 mm, with a minimum reflection loss of −51.2 dB. The strategy was further extended to multiple 3d transition metals (Cr, Mn, Co, Ni, Cu, and Zn). Results indicate that Group VIII elements (Fe, Co, Ni) exhibit superior performance in practical materials due to their electronic structures that favor balancing polarization and conduction losses. Radar cross section simulations confirm the exceptional attenuation capabilities of this series of absorbers in real-world scenarios. This work not only pioneers new applications for GDY in microwave absorption but also establishes a theoretical foundation for rationally designing atomically precise electromagnetic functional materials by revealing the “single-atom structure–property” correlation. Highlights: 1 The metal single-atom doping strategy was systematically applied to graphdiyne (GDY), an emerging two-dimensional carbon material, and a series of M-N-GDY single-atom microwave absorbers were successfully fabricated for the first time. 2 Combining X-ray absorption fine structure and density functional theory calculations, the influence of the central atom coordination structure (FeN2C2, FeC4) on the overall electronic properties was elucidated. 3 The optimal sample Fe-N-GDY achieved an effective absorption bandwidth of 5.98 GHz at a matched thickness of 2.0 mm, with a minimum reflection loss of -51.2 dB.